From positive to death : a corpus-based semantic analysis of COVID-19 representation in Malaysian English news reports - Chang, Li Xin; Hajar Abdul Rahim, (Penerbit Universiti Kebangsaan Malaysia, 2021)
More than a year after being declared a pandemic, Covid-19 has not shown any sure signs of dissipating even as the battle to curb it continues. In Malaysia, the Movement Control Order (MCO), or lockdown seems to be the most effective way to curb the spread of the disease. Unfortunately, studies show that lockdowns affect people’s livelihoods and lifestyle, as well as their emotional and mental state. This situation, in many countries, is exacerbated by the onslaught of negative news on Covid-19 and heightened news consumption via various media platforms. Given this, the objective of the current study is to analyse the representation of Covid-19 in Malaysian media based on a corpus of news reports during Malaysia’s first lockdown, i.e. MCO 1.0. This was a period of uncertainty lasting six weeks beginning from 18 March 2020 which saw increased reports of mental health cases and domestic violence cases in the country. News reports published in two Malaysian English online newspapers, The Star Online and Malaysiakini during MCO 1.0 formed the corpus of study. Using collocational analysis, the study examined the semantic prosody of Covid-19 and how it is represented in Malaysian new reports. The findings show that ‘Covid-19’ generally occurs in the company of unfavourable associations, causing it to acquire a negative prosody and in turn negatively represented in the news reports. The unfavourable portrayal of Covid- 19, coupled with the increase in news consumption may adversely affect readers’ emotions and anxiety levels, which in turn, may contribute to crisis fatigue.